Perbandingan Perlakuan Pajak Penghasilan Untuk Dokter Dengan Status Pegawai Negeri Dan Dokter Dengan Status Pegawai Swasta: Studi Kasus Pada Dr. N Dan Dr. S - Rizki Alaika (Majalah Bisnis & IPTEK, 2020)
This study aims to analyze the imposition of Income Tax for doctors with civil servant status or private employees and analyze whether there are similarities and differences in the imposition of Income Taxes between doctors with civil servant status or private employees. Data used by researchers, namely primary data and secondary data. The research method used is descriptive research method. The results of the study show that domestic individual taxpayers who are doctors with status as civil servants or private employees can be subject to final income tax, not final, or not subject to income tax on income earned. There are similarities and differences in the imposition of income tax between domestic individual taxpayers who are doctors with status as civil servants and private employees.